2019
DOI: 10.1038/s41598-019-49960-x
|View full text |Cite
|
Sign up to set email alerts
|

The specific seroreactivity to ∆Np73 isoforms shows higher diagnostic ability in colorectal cancer patients than the canonical p73 protein

Abstract: The p53-family is tightly regulated at transcriptional level. Due to alternative splicing, up to 40 different theoretical proteoforms have been described for p73 and at least 20 and 10 for p53 and p63, respectively. However, only the canonical proteins have been evaluated as autoantibody targets in cancer patients for diagnosis. In this study, we have cloned and expressed in vitro the most upregulated proteoforms of p73, ΔNp73α and ΔNp73β, for the analysis of their seroreactivity by a developed luminescence ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…This last limitation could produce the misidentification of relevant TAAs, which could be overcome by immunoprecipitation. Here, among the identified proteins as potential autoantibody targets in CRC (Table 2), we observed the presence of at least one protein containing continuous and discontinuous epitopes -p53-, as it has been previously demonstrated by ELISA, WB and protein microarrays [23,29,43], and thus supporting our approach to identify TAAs avoiding conformational limitations.…”
Section: Discussionsupporting
confidence: 85%
“…This last limitation could produce the misidentification of relevant TAAs, which could be overcome by immunoprecipitation. Here, among the identified proteins as potential autoantibody targets in CRC (Table 2), we observed the presence of at least one protein containing continuous and discontinuous epitopes -p53-, as it has been previously demonstrated by ELISA, WB and protein microarrays [23,29,43], and thus supporting our approach to identify TAAs avoiding conformational limitations.…”
Section: Discussionsupporting
confidence: 85%
“…We previously analyzed the potential seroreactivity of different variants of the p53 family (p53, p73, ΔNp73α, and ΔNp73β) [ 35 ] in a subset of our current cohort (healthy, n = 15; PL, n = 19; CRC, n = 9). Here, the correlation between the autoantibody levels and the ΔNp73 and Δ133p53 EV content was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…In our attempt to identify biomarkers for the early detection of CRC and the plausible usage of the TP53 family members to this aim, we have recently described a significant difference in the seroreactivity for ΔNp73 between CRC patients and subjects with PL versus healthy controls [ 35 ]. Interestingly, we have not observed a correlation between ΔNp73 seroreactivity and EVs’ mRNA levels of ΔNp73, TAp73 and Δ133p53, although a trend is observed for the negative association between the levels of ΔNp73 autoantibodies and EVs’ ΔNp73 mRNA in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This negative regulation by DNp73 forms an autoregulatory feedback loop, since both TAp73 and p53 can induce expression of DNp73 isoforms by direct binding to the P2 promoter (Irwin, 2006;Rufini et al, 2011;Di et al, 2013). A newest evidence showed that DNp73 isoforms has higher applicant potential in colorectal cancer patients than the canonical p73 protein (Garranzo-Asensio et al, 2019). Thus, it is reasonable to focus on DNp73.…”
Section: Resultsmentioning
confidence: 99%